The Asynchronous Cookbook (Open textbook library., 2021)
Whether you're teaching mostly in person but looking for some regular, asynchronous activities to add to your course, or teaching a fully online course, this resource is for you. The activities in this cookbook draw on research and good practice in online course design to provide recipes - concise and specific instructions and examples - for adding asynchronous activities to a course. Meaningful interaction between students and instructors is a key ingredient in all of these recipes.